Comparison of ciprofol (HSK3486) versus propofol for the induction of deep sedation during gastroscopy and colonoscopy procedures: A multi‐centre, non‐inferiority, randomized, controlled phase 3 clinical trial. Issue 2 (10th June 2022) - Li, Junxiang; Wang, Xiao; Liu, Jin; Wang, Xia; Li, Xiangkui; Wang, Yaping; Ouyang, Wen; Li, Jun; Yao, Shanglong; Zhu, Zhaoqiong; Guo, Qulian; Yu, Yonghao; et al.
Abstract: Ciprofol is a propofol analogue with improved pharmacokinetic properties. A multi‐centre, non‐inferiority trial was conducted to compare the deep sedation properties of ciprofol and propofol with a non‐inferiority margin of 8% in patients undergoing gastroscopy and colonoscopy. In total, 289 patients were randomly allocated for surgery (259 colonoscopy and 30 gastroscopy) at a 1:1 ratio to be given intravenous injections of ciprofol (0.4 mg/kg) or propofol (1.5 mg/kg). The primary outcome was the success rate of colonoscopy defined as colonoscopy completion with no need for an alternative sedative or >5 ciprofol or propofol top up doses within any 15‐min time period. The success rate of colonoscopy was 100% in the ciprofol group vs. 99.2% in the propofol group (mean difference 0.8%, 95% CI: −2.2% to 4.2%). Except for the gastrointestinal lesions found during the gastroscopy and colonoscopy procedures, the occurrence rates of adverse drug reactions in the ciprofol and propofol groups were 31.3% and 62.8%, respectively ( P < 0.001). Pain on injection was less common in the ciprofol group (4.9% vs. 52.4%, P < 0.001). The outcomes demonstrated that ciprofol was non‐inferior to propofol with regard to successful sedation for gastroscopy or colonoscopy procedures and no obvious important adverse events occurred.